The first-in-class pro-apoptotic peptide PEP-010 is effective in monotherapy and in combination with paclitaxel on resistant ovarian adenocarcinoma cell models - Lacroix, Aline; Farhat, Rayan; Robert, Aude; Brenner, Catherine; Wiels, Joëlle; Germini, Diego (Frontiers in Pharmacology, 2024)
Ovarian adenocarcinoma is the gynecological malignancy with the worst prognosis and the highest mortality rate. In the first stages of treatment, chemotherapy results effective, but its prolonged use and high doses lead to the appearance of resistance to treatments and relapse in most patients, representing a major challenge for clinicians. We developed PEP-010, a cell-penetrating proapoptotic peptide disrupting the protein-protein interaction between caspase-9 and protein phosphatase 2A, thereby leading to the recovery of their activity in the apoptotic pathway. We show here that PEP-010 effectively induces cell death in monotherapy in up to 55% of cells from ovarian adenocarcinoma cell models resistant to different chemotherapies. Moreover, when used in combination with paclitaxel, one of the therapeutic options for recurrent ovarian carcinoma, PEP-010 showed a beneficial effect leading to the reduction of the IC50 of paclitaxel of 2.2 times and to apoptosis in 87% of cells. The described results suggest the potential therapeutic interest for PEP-010 and lead to the choice of ovarian adenocarcinoma as one of the major indications of the ongoing clinical trial.